Experimental investigation on the thermo-hydrodynamics of oscillatory meniscus in a capillary tube using FC-72 as working fluid. (October 2015) - Recklin, Viktor; Pattamatta, Arvind; Stephan, Peter
Highlights: Oscillatory pattern of single meniscus in capillary tube for FC-72 is observed. At high evaporator temperature double peak in the pressure oscillation is noticed. Oscillation depends on the temperatures of reservoir, evaporator and condenser. Increase in evaporator temperature by 20 °C results in a pressure increase by 600%. There is a strong dependency of the thermal resistance on heat exchanger lengths.